THEORETICAL BASIS OF IMPROVING CREATIVE ACTIVITY IN STUDENTS (Academicia Globe: Inderscience Research, 2022)
In this article, the essence of the concept of creativity, the problems of researching the problem of developing creative thinking, creative activity among students of higher education institutions, and recommendations for increasing creativity are developed.